Dyslipidemia Increases the Risk of Severe COVID-19: A Systematic Review, Meta-analysis, and Meta-regression. (March 2021) - Atmosudigdo, Indriwanto Sakidjan; Lim, Michael Anthonius; Radi, Basuni; Henrina, Joshua; Yonas, Emir; Vania, Rachel; Pranata, Raymond
Objective: This systematic review and meta-analysis aimed to evaluate whether dyslipidemia affects the mortality and severity of COVID-19, we also aimed to evaluate whether other comorbidities influence the association. Methods: A systematic literature search using PubMed, Embase, and EuropePMC was performed on 8 October 2020. This study's main outcome is a poor composite outcome, comprising of mortality and severe COVID-19. Results: There were 9 studies with 3663 patients. The prevalence of dyslipidemia in this pooled analysis was 18% (4%-32%). Dyslipidemia was associated with increased composite poor outcome (RR 1.39 [1.02, 1.88], P = .010; I 2 : 56.7%, P = .018). Subgroup analysis showed that dyslipidemia was associated with severe COVID-19 (RR 1.39 [1.03, 1.87], P = .008; I 2 : 57.4%, P = .029). Meta-regression showed that the association between dyslipidemia and poor outcome varies by age (coefficient: −0.04, P = .033), male gender (coefficient: −0.03, P = .042), and hypertension (coefficient: −0.02, P = .033), but not diabetes (coefficient: −0.24, P = .135) and cardiovascular diseases (coefficient: −0.01, P = .506). Inverted funnel-plot was relatively symmetrical. Egger's test indicates that the pooled analysis was not statistically significant for small-study effects ( P = .206). Conclusion: Dyslipidemia potentially increases mortality and severity of COVID-19. The association was stronger in patients with older age, male, and hypertension. PROSPERO Registration Number: CRD42020213491